The Brazilian class C women perception regarding premium mass products in the beauty industry - Prados, Camila da Silva (2015)
Recently, emerging markets became a potential target for the beauty industry and Brazil is becoming a profitable market for premium cosmetic products (Euromonitor International, 2013). The low-income population in Brazil represents 70% of its inhabitants when considering classes C, D and E (Barki and Parente, 2010), being the class C represented by 56% of the population (Neri, 2012). This is a potential market for the multinational companies (MNCs) that face challenges to do business in there since class C choose to spend part of their income with products related to beauty (Silva and Parente, 2007) and there is still a little knowledge about the BoP consumption behavior. Therefore, the objective of this study is to investigate and describe the consumption behavior of the Brazilian women class C in the beauty sector related to premium-mass products, gaining a deeper knowledge in regards to this population and the subject proposed. To reach this objective, the author used a methodology based on a qualitative descript analysis in which 20 women from all age groups belonging to the Brazilian class C were interviewed and quotes were used to provide the confirmation of the analysis’ results. The results suggest that, over the years, there was indeed a trade up movement in the consumption of the beauty products. In addition, five main aspects were identified, which drive the class C women’s purchase decision in the beauty sector: reliability, quality, status, self-esteem and well-being. Despite of the limitations of an exploratory study, this research will be expected to increase the knowledge about the BoP market, especially in regards to the beauty industry.